2020
DOI: 10.1002/eng2.12142
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of fluid flow and heat transfer characteristics in solar air collector with curved perforated baffles

Abstract: In this article, an improved double-pass solar air heater with multiple curved perforated baffles is proposed; the solar air heater can enhance the heat transfer between air and heat absorber plate sufficiently by using a perforated baffles. At the same time, to reduce the flow resistance of air, a curved shape was created on the baffles. This research is aimed at evaluating a novel solar air heater design in terms of its thermal efficiency and temperature distributions within the solar air heater in forced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Experimental studies on different modifications for multipass SAH have been performed to demonstrate their effectiveness [24][25][26]. In addition, with the development of numerical algorithms and computer processors, CFD (computational fluid dynamics) studies have been conducted to reduce the experimental time and costs [27][28][29][30][31]. More recently, Heydari et al [32] proposed and numerically examined a novel helical airflow path around triangular channels.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on different modifications for multipass SAH have been performed to demonstrate their effectiveness [24][25][26]. In addition, with the development of numerical algorithms and computer processors, CFD (computational fluid dynamics) studies have been conducted to reduce the experimental time and costs [27][28][29][30][31]. More recently, Heydari et al [32] proposed and numerically examined a novel helical airflow path around triangular channels.…”
Section: Introductionmentioning
confidence: 99%
“…El-Said [89] numerically studied the heat transfer behavior of air in a perforated baffle attached to an absorber plate (shown in Figure 20) at a certain angle using Navier-Stokes and energy equations. It was found that the thermal efficiency and outlet temperature increased and pressure was decreased by enhancing the hole diameter of the baffle, while both parameters reduced by raising the baffle inclination angle to a maximum efficiency of 77%, which was achieved at a 3 mm diameter, 7 • angle, and 0.07 kg/s flow rate.…”
Section: Baffle Shapesmentioning
confidence: 99%
“…Saravanakumar (2020) used arc shaped rib and Wang (2020) suggested "S" shaped ribs with gap for enhancing the rate of convection heat transfer. Another way for enhancing heat transfer is using baffles with different shapes, such that this technique was examined by Bayrak (2013), El-Said (2020), Fiuk (2019), Hachemi (1995), Chabane (2014) and Yang (2014). Replacing flat plate absorber with V-groove corrugated absorber is another method for performance improvement and many investigators including Ho (2017), Desisa (2020) and El-Sebaii (2011) studied about this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Another way for enhancing heat transfer is using baffles with different shapes, such that this technique was examined by Bayrak (2013), El-Said (2020), Fiuk (2019), Hachemi (1995), Chabane (2014) and Yang (2014). Replacing flat plate absorber with V-groove corrugated absorber is another method for performance improvement and many investigators including Ho (2017), Desisa (2020) and El-Sebaii (2011) studied about this technique. A numerical analysis of solar air dryer with a V-groove double pass collector carried out by Hassan (2022) and the obtained findings which revealed the positive effect of the applied method were validated with experiment.…”
Section: Introductionmentioning
confidence: 99%